Aplikasi Reminder Jadwal Kerja Untuk Pekerja Casual Berbasis Android (Studi Kasus : Grand City Convention & Exhibition Surabaya) - Rizal Dwi Baskoro; Firman Hadi S Pratama (Melek IT : Information Technology Journal, 2017)
Application Reminder work schedule for casual workers is an Android-based application that serves as a reminder of the work schedule for casual workers. Casual workers are workers who work only when needed, just in case they were called Crowded and paid daily. In everyday life generally, casual workers often forget to organize and stay on the daily schedule. Therefore, the author makes this application to be able to remind the casual workers wherever and whenever they are with their smartphones. One way is to leverage the power of Android smartphones that they have because it is not uncommon for a short business casual in the modern era is hard to be separated from their gadgets. For that, we need an application that can be partners who can remember their schedule.